SOUND SUBSTITUTION AND MODIFICATION IN BORROWING - Ruziev Khusniddin Bakhritdinovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article examines sound substitution and modification in borrowing foreign words. It shows how consonants, vowels, syllables, and stress are adapted to fit English phonology. Examples illustrate these changes, ensuring borrowed words are pronounceable and integrated.